KEPEMIMPINAN SITUASIONAL: STUDI KASUS DI MADRASAH LAB SCHOOL UNIVERSITAS ISLAM BUNGA BANGSA CIREBON - Khoriah, Aah; Nursamsy, Dede; Muna, Hana Zakiyyatul; Putri, Nurul; Umamah, Uum (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2023)
The purpose of this study was to review the application of situational leadership in Madrasah Lab School of Bunga Bangsa Islamic University Cirebon. The method used in this research is a case study. The results showed that the adaptive leadership style carried out by the head of the madrasah based on the principles of adaptive leadership which includes the application of context understanding, long-term thinking principles, the principle of commitment to sustainable change, and the principle of continuous learning has been done well. This can be seen from the aspect of understanding the context that the establishment of this school was due to the identification of the needs of local residents for the existence of an ibtidaiyah madrasa. The aspect of long-term thinking can be seen from the strategic plan made for the future development of madrasah. The aspect of sustainable commitment is assessed from the large number of teachers who are still teaching from the beginning of the establishment of the madrasah. Meanwhile, the continuous learning aspect has not been fully implemented because it still focuses on the development of students.Keywords: Situational leadership; Madrasah; Lab School.